Transformasi Pendidikan dan Perubahan sosial-budaya Pada Masa Pergerekan Nasional - Muhamad Nur Khabib; Ahmad Ruslan; Desvian Bandarsyah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
This paper is made to analyze and describe how the changes that occurred before and after the national movement took place. Such as social, cultural, and educational aspects. The national movement is one of the first steps in achieving independence. Along the way, when ethical politics began to be implemented in the Dutch East Indies, changes began to occur in various sectors. The colonial government began to open up opportunities for young people to get access to education. This eventually triggered the growth and development of an educated society which became the forerunner of the driving force of the national movement. The struggle carried out by the students is to educate the lives of the indigenous people and struggle through diplomacy to strengthen the existence of the Indonesian nation. They reject the struggle through armed contact, considering the long history of this nation which has never succeeded in fighting the Colonial Government using weapons.